The impact of digitization on the level of electronic professional development for teachers in light of the availability of its tools and the ability to use them from the teachers’ point of view - Al-Baher, Ibrahim Ali; Albanadreh, Shireen Mohammad (Eximia, 2022)
The current study aimed to know the impact of digitization on the level of Electronic professional development for teachers in light of the availability of its tools and the ability to practice them from the teachers’ point of view ,The study sample consisted of (150) male and female teachers, who were selected in a stratified random manner The descriptive survey method was used in the current study, To achieve the objectives of the study, a questionnaire was developed, and its validity and reliability were confirmed. The results showed that the effect of digitization on the level of electronic professional development for teachers was medium, and the results of the study showed that there were statistically significant differences at the significance level (a </= 0.05) according to the gender variable in favor of the female category. And there were no statistically significant differences according to the variable years of experience, and there were no statistically significant differences according to the educational qualification variable In light of these results, the study recommended that the Ministry of Education attach great importance to digitization and its tools so that it works to stimulate conducting studies and research from time to time, To study the nature and conditions of educational work and its need for professional development of teachers through the use of the digital technological aspect.